Alcohol as a public health threat in Poland: rising consumption, weakening policy, and increasing mortality - Janik-Koncewicz, Kinga; Zatoński, Witold (Journal of Health Inequalities, 2025)
Alcohol consumption is one of the most significant modifiable risk factors affecting global health. In Poland, alcohol-related diseases have become a major public health challenge, reflected in rising consumption levels and rates of alcohol-related morbidity and mortality, as well as increased availability and affordability. Although alcohol is widely accepted socially, it is a psychoactive, addictive, toxic, and carcinogenic substance associated with over 200 diseases. Even small amounts increase the risk of chronic non-communicable diseases, mental disorders, and cancer. In 2019, alcohol caused approximately 2.6 million deaths globally and more than 115 million disability-adjusted life years (DALYs). Poland is one of the few European countries where alcohol consumption has increased steadily since the early 2000s. This rise has been strongly influenced by the weakening of policy measures, including reduced excise taxes leading to higher affordability, liberalized advertising regulations, 24/7 availability, and the introduction of small-bottle spirits. As affordability and exposure grew, alcohol-related morbidity and mortality followed. Alcoholic liver cirrhosis (that is, fully attributable to alcohol) illustrates this trend clearly: between 1999 and 2022, mortality rose several-fold across all adult age groups, particularly among women and older adults. Alcohol-related cancers and injuries also increased. While many European countries have reduced consumption through strict regulation, Poland has weakened previously effective control measures. World Health Organization assessments highlight insufficient action on taxation, availability, and marketing restrictions, which has contributed to worsening epidemiological trends. Effective alcohol harm reduction requires comprehensive public health strategies: regular excise tax increases, strict advertising bans, limits on availability, and well-funded national educational programmes. Raising public awareness is essential, as many Poles remain unaware that even light drinking increases cancer risk. Restoring a robust national alcohol policy, aligned with international standards and focused on prevention, monitoring, and population-wide risk reduction, is crucial for reversing the ongoing health crisis in Poland.